Headaches in Childhood - Aydin, Mustafa; Bozdag, Senol; Kabakus, Nimet (Ortadogu Ad Pres & Publ Co, 2010)
Objective: This study aims to investigate the incidence, etiological factors, response to treatment and the prognosis of the childhood headaches on the ground of the diagnostic criteria of the International Classification of Headache Disorders, 2nd Edition (ICHD-II, 2004). Material and Methods: One hundred thirty three cases diagnosed with headaches based on the diagnostic criteria of ICH (D) over tilde II, 2004 were selected from a total of 5300 patients that applied to the pediatric neurology outpatient clinic during last six years. Results: The children that were diagnosed with headache constituted the %2.9 of pediatric neurology patients group. The average age of the patients were 11.1 +/- 3.2 years (range: 3.3-17 years). There were 74 girls (%55.6) and 59 boys (%44.4). The children with migraine constituted more than half of the patients (n:77, %58). After migraine, sinusitis (n:22, %16,5), tension type headache (n:16, %12), and epilepsy (n:7, %5.3) were the most frequent causes of headaches, respectively. About half of the patients (n:44, %47.8) suffered from decrease in school performance along with headaches. It was detected that a considerable number of the patients (n:111, %83.5) benefited from one of the treatment modalities. Conclusion: These results show that (i) headaches are a common problem of childhood that affect negatively the life quality and the school performance, (ii) the need for neurophysiological and neuroradiological methods can be reduced with a good physical and neurological examination, (iii) headaches in childhood are mostly curable problems.
Çocukluk ça?ı; baş a?rı;ları;
Keywords: Headache; etiology; migraine disorders; child